Improving Learning Outcomes To Hit The Ball In Castle Games Through Play Methods In Class Iv Students Of Waesama 17 Private Elementary School - Jamatia Fatsey; Idris Moh. Latar; Emma Rumahlewang (International Journal of Education, Information Technology, and Others, 2023)
The purpose of this research is to improve the learning outcomes of hitting the ball in a baseball game through the playing method for fourth graders of Waesama 17 Private Elementary School. The research method used in this research is to use classroom action research. The subjects of this study were 18 grade IV students of Waesama Private Elementary School 17. After processing and analyzing the data, the results of the first cycle were obtained based on the table of learning outcomes in the first cycle, there were 11 students who had completed 61.1%, while 7 students had not completed 38.8%. Cycle II based on the recapitulation table of student learning completeness in cycle II there were 18 students who completed or (100%) and there were no students who did not complete or (0%). From the results of the analysis and calculation of the data, it can be concluded that the playing method is effective for increasing the learning outcomes of hitting the ball in a baseball game for fourth graders of Waesama 17 Private Elementary School